SPATIAL ANALYSIS OF ROAD TRAFFIC ACCIDENT HOTSPOTS AND PATTERNS IN MUSCAT, OMAN: AN EXPLORATORY RISK MANAGEMENT ASSESSMENT - Alhajri, Bashayar; Abdul Rasam, Abdul Rauf; Tarudin, Nur Farizan; Khalid, Nafisah; Alshukaili, Dhafir (PLANNING MALAYSIA, 2024)
Oman is grappling with a significant challenge posed by road accidents, with approximately 1,539 accidents recorded in 2021. To tackle this issue, this study showcases the potential of Geographical Information Systems (GIS) technology in mapping and analysing road accident hotspots and distribution patterns in Muscat, Oman. The data (from 2019 to 2021) was gathered from the Omani Royal Police Department, with ArcGIS Pro serving as the geographical representation and analysis platform. The study identified high-risk locations for road accidents in specific areas of Mutrah, Bawshar, and Al-Amerat, which were attributed to densely populated areas and heavy traffic flow. The spatial pattern of accidents appeared dispersed, with Fridays and Mondays recording the highest number of accidents due to increased traffic associated with social gatherings and commuting to work or school after the weekend. Qualitative effect analysis revealed that factors such as roadway characteristics, environmental conditions, traffic volume, driver behaviour, and vulnerable road users may influence local accident hotspots. These GIS-based road accident analyses can enhance road accident guidelines and traffic prevention strategies in the Muscat region.